A theology of holiness historical, exegetical, and philosophical perspectives - Goldstein, Alec (New York, NY Kodesh Press L.L.C, 2018)
"The idea of 'holiness' is central to religion, but it is also one of the hardest concepts to define. Is 'holiness' a synonym for Godliness, one of God's attributes, or does it have independent existence? What does it mean to say that both God and man are holy? What is the proper understanding of 'Be holy, because I the Lord your God am holy'? A Theology of Holiness analyzes the meaning of the Hebrew root k-d-sh from ancient sources, throughout Tanakh, the Talmud, Rashi, Maimonides, Nachmanides, Rabbi Samson Raphael Hirsch, and Rabbi Joseph B. Soloveitchik. Ultimately, it is a work of theology, and helps the reader achieve a deeper understanding of holiness"--Page 4 of cover
Includes bibliographical references (pages 248-258)
Keywords: Holiness -- Judaism; Holiness -- Biblical teaching; God (Judaism) -- Attributes; Holiness -- Judaism; Holiness -- Biblical teaching; Ḳdsh (The Hebrew root); God (Judaism) -- Attributes; Judaism -- Theology; Holiness - Judaism; God (Judaism) - Attributes; Holiness - Biblical teaching; Holiness - Judaism; Holiness - Biblical teaching; God (Judaism) - Attributes; God (Judaism) ; Attributes; Holiness ; Biblical teaching